The Interferon (IFN) Class of Cytokines and the IFN Regulatory Factor (IRF) Transcription Factor Family - Negishi, Hideo; Taniguchi, Tadatsugu; Yanai, Hideyuki (Cold Spring Harbor perspectives in biology, 2018)
Interferons (IFNs) are a broad class of cytokines elicited on challenge to the host defense and are essential for mobilizing immune responses to pathogens. Divided into three classes, type I, type II, and type III, all IFNs share in common the ability to evoke antiviral activities initiated by the interaction with their cognate receptors. The nine-member IFN regulatory factor (IRF) family, first discovered in the context of transcriptional regulation of type I IFN genes following viral infection, are pivotal for the regulation of the IFN responses. In this review, we briefly describe cardinal features of the three types of IFNs and then focus on the role of the IRF family members in the regulation of each IFN system.